2020
DOI: 10.5539/ijb.v12n3p18
|View full text |Cite
|
Sign up to set email alerts
|

Ants Can Acquire Multiple Symbolisms

Abstract: The workers of the ant Myrmica sabuleti were previously shown to be able to associate a given amount to its corresponding symbol, one symbol at a time. It was here examined if they can simultaneously learn to associate the amount 1 with a corresponding symbol, the amount 2 with another symbol, the amount 3 with a third symbol, and the amount 4 with a fourth symbol, the cue to avoid being the amount 5. Thanks to operant conditioning during 156 hours and twelve successive testing experiments, it was shown that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, bees can also acquire numerical symbolism: they can associate shapes not evoking numerosities with a given number of elements (2 or 3 elements) (Howard, Avarguès-Weber, Garcia, Greentree, & Dyer, 2019c). As for the ant M. sabuleti, we have shown that they can acquire single (Cammaerts & Cammaerts, 2020b) as well as multiple numerical symbolisms (Cammaerts & Cammaerts, 2020c).…”
Section: Introductionmentioning
confidence: 78%
“…However, bees can also acquire numerical symbolism: they can associate shapes not evoking numerosities with a given number of elements (2 or 3 elements) (Howard, Avarguès-Weber, Garcia, Greentree, & Dyer, 2019c). As for the ant M. sabuleti, we have shown that they can acquire single (Cammaerts & Cammaerts, 2020b) as well as multiple numerical symbolisms (Cammaerts & Cammaerts, 2020c).…”
Section: Introductionmentioning
confidence: 78%
“…While studying the ants' acquisition of multiple numerical symbolisms, a distance effect was observed in the ants' responses since they were trained to the numbers 1 to 4 faced with the number 5 (Cammaerts & Cammaerts, 2020d). Quite the reverse, while studying the ants' adding up symbols, no distance effect was observed since the ants were trained with numbers 1 to 4 versus zero (Cammaerts & Cammaerts, 2020e).…”
Section: Discussionmentioning
confidence: 99%